THE DETERMINANTS AFFECTING FRAUD TRENDS - Seto Satriyo Bayu Aji (Asia Pacific Fraud Journal, 2018)
This study aims to examine the determinants that influence the tendency of fraud in medium-sized companies in Yogyakarta. The variables used in this study are ethics, compensation conformity, leadership stlye, and fraud. The population in this study is medium-sized companies in Yogyakarta. Sampling is done by using purposive sampling method. The sample used is the staff of medium-sized companies in Yogyakarta. The research model uses SmartPLS 2.0 in proccesing data. The results of this study show that ethics has a negative effect on fraud; compensation conformity has a negative effect on fraud; and leadership style has a negative effect on fraud.